THE INFLUENCE OF PARENTAL CLASS ON EARLY CHILDHOOD CLEAN AND HEALTHY LIVING BEHAVIOR - Ani Mulyani; Rivo Panji Yudha; Nor Ilman Syaputra; Lina Marlina; Uswatun; Nihayaturaochmah; Yulyati Mulyanto; Adolfiron Luji (International Conferences on Early Childhood Education Proceedings, 2024)
This study aims to determine the effect of the implementation of parent classes on clean and healthy living behavior of children aged 5-6 years in SPS Yaman Nurjati, Kertasmaya District, Indramayu Regency. This study used Pre-Experimental Designs with One Group Pretest-Posttest Design. One Group Pretest-Posttest Design. Researchers also conducted validity and reliability tests. Based on statistical data analysis paired sample t-test. The calculated t value is 10.793 with a significance value (2-tailed) of 0.001. Based on these data that the value of 0.001 <0.05, thus it can be concluded that the implementation of parental classes affects the clean and healthy behavior of early childhood.